2022
DOI: 10.3389/fenrg.2022.866037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Operational Stability of Centrifugal Pumps of Varying Impeller Types Based on External Characteristic, Pressure Pulsation and Vibration Characteristic Tests

Abstract: This study performed external characteristics, dynamic pressure, and vibration tests on the closed impeller model, semi-open type impeller model, and open impeller model in order to study the influence of the impeller structure on the operational stability of the pump. According to the research findings, the external characteristics of the three impellers enjoyed favorable stability with flat curves under low flow rates. As the flow increases, the stability of the external characteristics weakens, and the poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To compare the pressure pulsations of the fire pump at different flow rates more intuitively, the pressure pulsation coefficient C p 17,18 was introduced to measure the magnitude of the pressure pulsations as followswhere P is the static pressure at a certain time, P¯ is the average static pressure, u is the circumferential speed of the impeller outlet, and ρ is the density of the water.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the pressure pulsations of the fire pump at different flow rates more intuitively, the pressure pulsation coefficient C p 17,18 was introduced to measure the magnitude of the pressure pulsations as followswhere P is the static pressure at a certain time, P¯ is the average static pressure, u is the circumferential speed of the impeller outlet, and ρ is the density of the water.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The pressure fluctuation information in a cycle under each flow rate was selected for analysis. To compare the pressure pulsations of the fire pump at different flow rates more intuitively, the pressure pulsation coefficient C p 17,18 was introduced to measure the magnitude of the pressure pulsations as follows…”
Section: Pressure Pulsation Analysismentioning
confidence: 99%
“…Jia et al [5] studied the impeller influence on the pump stability, analyzing three types of impellers: closed impeller, semi-open impeller, and open impeller. For higher flow rates, the closed impeller exhibited the highest stability, while the open impeller performed the least reliably.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of vibration, the area around the tongue was the least stable, with the closed impeller causing the least casing vibration, and the open impeller resulting in the highest vibration levels. Additionally, the interaction between the volute and the impeller influenced flow stability and led to fluctuations in pressure distribution around the circumference of the volute [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Ji et al [10] used the Wray Agarwal (WA) turbulence model to simulate the internal and external characteristics of centrifugal pump, and the results showed that the WA model could effectively calculate the energy performance of centrifugal pump under various working conditions, and had high accuracy. Jia et al [11] through research showed that with the increase of flow, the stability of the external characteristics of centrifugal pump decreases, the stability of open impeller was the worst, while the stability of closed impeller under large flow was the best, and the shell vibration of closed impeller was the smallest. Based on the N-S equation, Zhang et al [12] proposed a design method of a high-speed centrifugal pump.…”
Section: Introductionmentioning
confidence: 99%